Relatório de Estágio Profissional "No Caminho da Docência: transformando obstáculos em oportunidades" - Ana Margarida Faria da Silva (2018)
With the conclusion of this journey, arises now the opportunity to report the experiences felt throughout the Professional Internship. This first-person narrative is characterized by being a systematic analysis of the practical component that ought to mirror the feelings and the most striking episodes that happened, showing the methods of knowledge mobilization previously acquired as well as the respective practical application, therefore, it's about a final and reflective synthesis of all the process. As such, the present internship report reflects on the course of an internship student, in which she assumed the responsibility of teaching a 10th grade class. This journey had as stage a school in Santo Tirso that welcomed a three student internship program. Throughout this document, will be highlighted reflexions about the dilemmas, difficulties, doubts and decision-making that characterized the teaching and learning process, as well as the implemented strategies to raise the teaching efficiency. Upon a path of unrelenting learning, this document also contemplates sociometric and sociometric perception studies, centred in obtaining a more detailed knowledge of the particularities of each student and of the class as a group. The realization of this kind of study is important in order to obtain a better comprehension of the class and all its teaching-learning phenomenon's, thus obtaining a different perspective of the class beyond what is normally perceived, and be able to penetrate, in a distant way, into the student's social relationships. Lastly, the perception acquired throughout this journey, allowed to conclude that the growing complexity and diversity of today's society demands teachers to be more professionally prepared, and more autonomy to face different problems and challenges. The diversification of roles and responsibilities, as a result of several factors, defies teacher to new challenges. Teacher's functions goes beyond the mere conduction of the class during its teaching-learning process.